Integration of Green Accounting, Sustainability Disclosure, and Stakeholder Engagement on Company Performance - Ayu Lestari Setia Ningrum; Rum Hendarmin; Reny Aziatul Pebriani (Manunggal Halim Jaya, 2026)
This study analyzes the effects of green accounting integration, sustainability disclosure, and stakeholder engagement on company performance in the basic and chemical sectors listed on the Indonesia Stock Exchange during 2019-2023. Data were collected from 10 companies that consistently published sustainability reports for 5 years, yielding 50 report samples. Data analysis used multiple linear regression to test the effect of each variable. The results showed that green accounting integration had no effect on company performance with a significance value of 0.154 (>0.05). Sustainability disclosure also did not affect company performance, with a significance value of 0.824 (>0.05). Meanwhile, stakeholder engagement had an effect on company performance with a significance value of 0.001 (<0.05). Simultaneously, the three variables had a significant effect on company performance, with a significance value of 0.006 (<0.05) and an F table of 2.806, indicating that F count > F table (4.733 > 2.806), suggesting that the independent variables could explain variations in company performance. This research provides empirical evidence that sustainability practices such as green accounting and sustainability disclosure can improve company performance. However, stakeholder engagement requires a more integrated strategic approach to achieve significant impact. These results can guide company managers in designing effective sustainability policies.